Dear BioDaddy, an open letter - Ólafsdóttir, Stefanía (Taideyliopiston Teatterikorkeakoulu, 2023)
This written thesis is the companion of the live performance series ‘Dear BioDaddy,’, the fourth and ‘final’ iteration of which was presented at the New Performance Turku Biennale in September 2023. The work pivots in an autofictional & autoethnographical reflex around ‘BioDaddy’, the sperm donor who is my biological parent, confronting the complexities of assisted reproductive technologies, their violent histories and unexpected consequences, particularly within Scandinavia. The written component presented here provides the reader with the performance script whilst embedding within it expanded theoretical threads, poetic meanders and diaristic extracts. The task at hand became an act of allowing the text to perform itself, and point to itself as to employ a structural critique of kinship and nationhood through an unravelling of the thesis structure itself. As a performance lecture and a performative piece of writing, knowledge production is a topic of contention that is formally encountered in the text by utilising an alternative organising structure. Knowledge is therefore produced as a consequence of the interrelational and intertextual qualities of the texts and a play on their proximities. The texts carefully curate an encounter and an embrace of the paradoxes that manifest in ideas of the familial, and entangle the reader in a meta-structure of meanings whilst tracing my literary lineages in parallel with the techno-familial lineages I fiction along the way. This work is preoccupied with questions of multiplicity, belonging and uncertainty, and the reading of this thesis has perhaps been best described by my kindred as the experience of ‘passing through a feeling.’ As the work decomposes into a fictioning of ecosexual utopias, following a pilgrimage to inseminate the islands of the Earth, it searches not only for BioDaddy, but expanded kinships and alternative forms of community building, based on technological commonality and home-making in a beyond-human world.
Keywords: Assisted Reproductive Technologies; esittävät taiteet; performanssi; identiteetti; spermapankit; teatteritaide; lisääntyminen; biopolitics; feminismi; queer-kirjallisuus; kinship; reproduction; LAPS